Toward an understanding of the impacts of localized real case studies - Nkhoma, Mathers (Animo Repository, 2022)
This research aims to understand the mediating roles of learning engagement, learning process and learning experience in influencing students' outcomes through case study pedagogy. It gathered students' responses to localised real case studies discussed in Information Systems classes. Case knowledge and perception were used to measure students' learning outcomes in order to determine the degree to which students induced course concepts and how they felt the cases impacted their understanding of the course. Revised student engagement questionnaire was used to measure various forms of engagement such as skills, emotion, participation, and performance while revised study process questionnaire served to assess the extent to which students used deep or surface approach to learning. Additionally, seven roles of feedback were used to analyse students' learning experience. Finally, group performance and individual's positive perceptions of group learning were tested to measure students' learning outcomes. Structural equation modelling was used to test the causal model. Analysis revealed that case knowledge and case perception had positive influence on students' skill engagement and emotional engagement but only case knowledge had a positive impact on the functions of feedback.